2022
DOI: 10.1590/1414-431x2022e12381
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-(2S, 4R)-trans-4-hydroxy-L-proline, the major bioactive compound from Sideroxylon obtusifolium, attenuates pilocarpine-induced injury in cultured astrocytes

Abstract: Glial cells have been implicated in temporal lobe epilepsy in humans and in its models. Astrocytes are lost in several brain regions after acute seizures induced by pilocarpine and may suffer hyperplasia at subsequent time points. This study investigated the effect of N-methyl-(2S,4R)-trans-4-hydroxy-L-proline (NMP) on astrocytes exposed to cytotoxic concentrations of pilocarpine. Astrocytes were incubated with pilocarpine (half maximal inhibitory concentration (IC 50 )=31.86 mM) for 24 h. Afterwards, they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although the changes in astrocyte inflammation and oxidative stress can be observed in the epilepsy model, few studies have used PP as an astrocyte inducer in epilepsy models in vitro. Aquino and his colleagues claimed that PP significantly inhibited the viability of astrocytes and up‐regulated intracellular lipid peroxidation (Aquino et al., 2022; Ramazi et al., 2020). According to previous studies, GFAP and C3 are preferentially expressed in lipopolysaccharide (LPS)‐induced A1 reactive astrocytes (Zamanian et al., 2012), while Ptx3 and S100a10 are preferentially expressed in A2 reactive astrocytes (Guo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the changes in astrocyte inflammation and oxidative stress can be observed in the epilepsy model, few studies have used PP as an astrocyte inducer in epilepsy models in vitro. Aquino and his colleagues claimed that PP significantly inhibited the viability of astrocytes and up‐regulated intracellular lipid peroxidation (Aquino et al., 2022; Ramazi et al., 2020). According to previous studies, GFAP and C3 are preferentially expressed in lipopolysaccharide (LPS)‐induced A1 reactive astrocytes (Zamanian et al., 2012), while Ptx3 and S100a10 are preferentially expressed in A2 reactive astrocytes (Guo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To establish the epilepsy model of astrocytes, we treated astrocytes with gradient PP and found that 1 mM PP induced a significant decrease in the viability of astrocytes, whereas 0.25–0.5 mM PP had no effect on the astrocyte viability. Notably, PP is often used as an inducer in a mouse or rat epilepsy model (Aquino et al., 2022; Garzillo & Mello, 2002; Hubbard et al., 2016; Levesque et al., 2021). Although the changes in astrocyte inflammation and oxidative stress can be observed in the epilepsy model, few studies have used PP as an astrocyte inducer in epilepsy models in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scavenging of reactive oxygen species (O2− and H2O2) by the nuclear factor erythroid 2-related factor 2 and heme oxygenase-1 (NRF2/HO-1) signaling pathway was the primary method to achieve the goal of anti-oxidation, and a promising factor for improving the cognitive impairment seen in AD [40]. Previous reports have shown that NMP exhibits antioxidant behavior towards cytoplasm ROS accumulation and mitochondrial membrane depolarization caused by pilocarpine [41]. In this study, our Western blot analysis revealed that injecting Aβ 1-42 led to a reduction in the expression of NRF2 and HO-1 in the cortexes and hippocampi of mice treated with amyloid beta.…”
Section: Discussionmentioning
confidence: 99%